Falls Efficacy Scale and Single Item Question: Screening Accuracy for Older Adults Residing in Nursing Homes. Issue 5 (20th October 2021) - Meimandi, Mahsa; Fadavi-Ghaffari, Mahsa; Taghizadeh, Ghorban; Azad, Akram; Lajevardi, Laleh
ABSTRACT: Objectives : The Falls Efficacy Scale (FES) has been developed to evaluate self-efficacy in avoiding falling during Basic Activities of Daily Living (BADL) and Single Item Question (SIQ) evaluates fear of falling (FOF) by asking a single question. These tools have some pros and cons, therefore, the present study aimed to evaluate and compare screening accuracy of Falls Efficacy Scale (FES) and Single Item Question (SIQ) in measuring FOF for older adults. Methods : A total of 100 older adult residents of nursing homes (males: N = 63) were evaluated with Falls Efficacy Scale-International (FES-I), FES, and SIQ via interview. Cutoff points and validity parameters were calculated for the FES and SIQ by using FES-I as a criterion measure. Results : In a moderate FOF threshold, the sensitivity rate of 81.82% and 43.18% were obtained for FES and SIQ, respectively. High sensitivity and specificity rate were obtained for both FES (sensitivity and specificity: 100%) and SIQ (sensitivity: 94.44%; specificity: 90%) in severe FOF threshold. Conclusions : The results of this study indicated that, compared to the SIQ, the FES is a better tool to identify FOF in both moderate and severe thresholds in first screening. Clinical Implications : The FES is a valid and sensitive tool to identify FOF in older adults.